Komunikasi Demokratis Dalam Membentuk Keluarga Harmonis (Perspektif Al Quran Surah Al-Imran Ayat 159) - Nasrudin Nasrudin (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2023)
A harmonious family is the dream of every family, especially in the current era, the number of divorce cases that are increasing in the family makes it difficult to realize a harmonious family. Divorce in marriage usually occurs due to lack of communication or misunderstanding in communication. One way to prevent misunderstandings in communication is to implement democratic communication in the family. This study aims to explain that the importance of democratic communication is carried out in the family which will be discussed in the perspective of the Al-Quran Soorah Al-Imran Verse: 159. The data used by the authors in this study are data obtained from literature studies. The approach used is the thematic interpretation of the Qur'an, namely the Soorah Al-Imran Verse 159. The results of this study indicate that there are four concepts of democratic communication contained in the Soorah Al-Imran Verse 159, namely being gentle, forgiving each other, respecting opinions and putting your trust in Allah SWT. These four concepts if implemented in the family will create a harmonious family.